2012
DOI: 10.1111/j.1742-1241.2012.03003.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms in heart failure correlate poorly with objective haemodynamic parameters

Abstract: Overall, the correlation between symptoms and objective parameters was weak. Because of low magnitude of relationship between symptoms to objective parameters, it was concluded that there are likely other factors determining the perception of symptoms in HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 11 publications
2
38
0
Order By: Relevance
“…This finding was unexpected but is consistent with Leidy 14 who suggests that functional capacity is more closely related to age and comorbidities, rather than a single condition or disease process. These results are also consistent with previous finding that symptoms and hemodynamic parameters are poorly correlated 53 …”
Section: Discussionsupporting
confidence: 93%
“…This finding was unexpected but is consistent with Leidy 14 who suggests that functional capacity is more closely related to age and comorbidities, rather than a single condition or disease process. These results are also consistent with previous finding that symptoms and hemodynamic parameters are poorly correlated 53 …”
Section: Discussionsupporting
confidence: 93%
“…peak oxygen uptake). Finally, Guglin 20 recently concluded that there was no association between HF symptoms and multiple clinical factors that predict morbidity and mortality, including peak oxygen uptake, LVEF, Nt-proBNP, right heart catheterization parameters, and echocardiographic parameters. Our approach was different from prior research in that our goal was to identify distinct and common profiles among integrated data on symptoms and hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…those derived from right heart catheterization, echocardiographic, cardiopulmonary stress test and laboratory parameters) and symptoms have collectively concluded that there is limited-to-no association between the two. 1520 In the absence of a single test for HF or responsiveness to HF therapies, clinicians must integrate objective and subjective data to personalize treatment strategies. 21 For example, integrating data on current heart function and physical symptoms may allow clinicians to tailor monitoring strategies and/or promote effective self-care behaviors to enhance the patient’s quality of life and reduce healthcare utilization.…”
Section: Introductionmentioning
confidence: 99%
“…1 There is a limited association, however, between what patients experience as physical symptoms and what we can measure objectively about the severity of HF, including metrics of pressure, flow, contractility, exercise capacity and heart chamber geometry. 27 Most of what we know about HF in general, and about the relationship between objective measures of heart function and symptoms in particular, is derived from studies predominated by men. There are, however, several important gender differences in HF.…”
Section: Introductionmentioning
confidence: 99%